Redeployment of Dental Core Trainees in the United Kingdom due to Coronavirus Disease 2019 - Patel, Misha; Menhadji, Payvand; Mayor, Serena (European Journal of Dentistry, 2020)
Objective The coronavirus disease 2019 (COVID-19) pandemic has affected professionals in all fields; none more so than medical and dental professionals. As dental core trainees (DCT) working in hospitals, we have been at the forefront of the crisis and one of the first in line for redeployment. Therefore, we decided to investigate the impact of COVID-19 on the redeployment of DCTs across the UK.Materials and Methods  Data for this study was collected and shared between three project researchers. All researchers were undergoing dental core training in Oral Surgery and Restorative dentistry at Guy’s Hospital, London. An online survey was sent out via email and online social media platforms to reach as many DCTs as possible in the United Kingdom. Implied consent was obtained by respondents on submission of the survey.The survey consisted of five sections and was branched, with respondents answering different sections depending on their redeployment status. No qualitative data was collected, as all questions included in the survey were dichotomous or multiple-choice questions. The last two questions were in the form of a 5-point Likert scale, inviting respondents to rate five statements from strongly agree to strongly disagree.Results A total of 150 participants responded, of which 34% had been redeployed due to the pandemic. The majority of DCTs were redeployed to an intensive care unit or similar setting, and over 75% of those redeployed were working with either COVID-19 positive/suspect patients. Additionally, 23.8% of respondents had stopped patient contact due to their medical status.Conclusion Many DCTs have been deployed to departments outside of their specialty and expressed some anxiety as a result. Inevitably, this has resulted in disruption to their training program and education over the last few months. The response across the United Kingdom has been understandably variable due to the differing demands of the hospital trusts within which the DCTs work.
Keywords: COVID-19; dental education; personal protective equipment; redeployment